NEW EFFICIENT MODEL-BASED PID DESIGN METHOD - Salem, Farhan A. (European Scientific Journal, ESJ, 2013)
Because of their simplicity, robustness and successful practical application, PID- controllers are the most popular and widely-used controllers in industry. Many PID design methods have been proposed, each has its advantages and limitations, However, finding appropriate parameters for the PID controller is still not easy task. This paper proposes a new simple and efficient model-based PID design method for achieving an important design compromise; acceptable stability, and medium fastness of response, the method is based on plant's parameters; the proposed PID design methodology was test, verified and compared using MATLAB/SIMULINK software.